Sublime, sublimação e expressão: a ressonância de Kant e Freud na articulação adorniana entre arte e sociedade - Proença, Fernanda (Rapsódia, 2020)
The present work intents to investigate Adorno’s aesthetic theory in regards to the relation between art and society, searching for points of convergence with the concepts of sublime in Kant and of sublimation in Freud. It aims to bring to light, at first, how the emancipatory aspect of the work of art depends on its non-subservience to reality, clarifying possible consonances and discrepancies with Freudian sublimation (understood as social adequacy) and with Kantian aesthetics (specially in its expectations of nature idoneity). Thereafter, in regards to the socio-historical aspect of art, investigate what art presents as extra-aesthetic in the development of the works’ truth content, articulating Adorno’s sedimentation and the mediated moments of aesthetic experience in Kant and Freud. At last, demonstrate how the utopian dimension of art as Adorno presents it depends on premises found in Freud and Kant, explicit in the primacy of imagination.